Did the Covid-19 Pandemic Affect Psychological Readiness to Return-To-Sport in Young Athletes Undergoing ACL Reconstruction?. Issue 5 (31st May 2022) - Christino, Melissa A.; Majumdar, Aditi S.; Coene, Ryan P.; Cook, Danielle L.; Kocher, Mininder S.; Kramer, Dennis E.; Micheli, Lyle J.; Yen, Yi-Meng; Milewski, Matthew D.
Background: Return-to-sport (RTS) following anterior cruciate ligament reconstruction (ACLR) is influenced by multiple physical and psychological variables. Psychological readiness has been associated with improved patient reported outcomes as well as RTS rates in young athletes. The COVID-19 pandemic may have altered the typical recovery process for patients undergoing ACLR. Hypothesis/Purpose: To compare 6-month postoperative levels of psychological readiness to RTS in ACLR patients before and during the pandemic. Methods: Patients were prospectively enrolled 6 months after primary ACLR at a single academic sports medicine practice, from December 2018 until May 2021. Patients were categorized into pre-COVID (enrollment prior to March 13, 2020) and COVID groups (March 13, 2020 - May 26, 2021). Demographic information, outcomes scores including the ACL-Return to Sport after Injury Scale (RSI) and PROMIS Psychological Stress Experiences (PROMIS-PSE), and physician RTS clearance were obtained and compared for both groups. Comparisons were performed utilizing Chi-square, Student's t-tests and linear regression. A matched analysis was conducted between groups controlling for age, sex, and graft type. Results: 231 patients were included in the present study (89 males, 142 females; mean age 16.9 years), with 76% (176/231) in the pre-COVID group and 24% (55/231) in the COVID group. There were no significant differences in age and sex between the two population cohorts. There was a significant difference in time from surgery to enrollment in the COVID group compared to the pre-COVID group (7.1 vs 6.2 months, p<0.001). In the matched cohort (n=126, 37/126 COVID group), the COVID group was cleared earlier by their physician to RTS compared to the pre-COVID group (6.9 months vs 8.5 months, p<0.001). While there was no significant difference between groups in 6 month ACL-RSI scores (63.8 pre-COVID vs 66.6 COVID, p=0.48), both groups yielded globally low scores. There were no significant associations between matched groups in PROMIS-PSE (p=0.71), IKDC (p=0.55), Pedi-IKDC (p=0.15), and Pedi-FABS (p=0.77) scores(Table 1) . Conclusion: Young athletes demonstrated similar levels of psychological readiness to RTS at 6 months following ACLR prior to and during the COVID-19 pandemic. Patient-reported outcome scores were similar in pre-COVID and COVID ACLR patients, suggesting that the pandemic may not have played a detrimental role in perceptions of recovery. Psychological readiness may not be fully optimized at 6 months post-ACLR and young athletes may benefit from additional time and training for progressive confidence, muscle strength, and performance. Table 1. Matched cohort outcomes comparing enrollment periods (n=126).